Affective well-being in the last years of life: the role of health decline - Schilling, Oliver; Deeg, Dorly; Huisman, Martijn (Psychology and aging, 2018)
Adding to recent evidence of terminal decline in affective well-being, this study examined the role of physical health in accounting for time-to-death-related changes in positive affect (PA) and negative affect (NA). We distinguished effects of preterminal health levels predicting levels ('preserved differentiation') and terminal changes ('differential preservation') and of terminal health declines predicting terminal changes ('terminal reactivity') of affective well-being in the terminal period of life. Data were used from the first cohort of the Longitudinal Aging Study Amsterdam, including 3-yearly measurements from 1992-1993 to 2011-2012 (N = 2310, age = 55-85 at baseline). Measures of PA and NA were derived from the Center for Epidemiologic Studies Depression Scale. Health measures included self-rated health, self-reported functional limitations, and gait speed. Exponential time-to-death-related trajectories in PA and NA were analyzed with mixed regression models. Results confirmed accelerated time-to-death-related decline of PA and increase of NA. Regarding health effects, the findings support terminal reactivity, in that the amount of end-of-life changes in affective well-being was closely linked to the concurrent terminal changes in health. Preterminal health levels did not predict the amount of terminal changes in affective well-being; however, reaching the final years of life with better levels of functional health appeared to promote longer maintenance of better levels of affective well-being and terminal declines more 'compressed' to a shorter period prior to death. The findings point to needs to strengthen individuals’ resources to compensate for health losses at the end of their life span. (PsycINFO Database Record (c) 2018 APA, all rights reserved)